Getting to know ArcGIS desktop : basics of ArcView, ArcEditor, and ArcInfo - Ormsby, Tim, 1958- (Redlands, Calif. : ESRI Press, 2004)
With revised material and new exercises based on ArcGIS version 9, this updated work acquaints geographers and GIS professionals with the principles of GIS as it teaches the mechanics of using ArcGIS software. Conceptual material is followed by scripted software exercises. Necessary GIS skills are presented in a variety of areas--map symbology, data overlay, map projection, and data conversion--as the making of maps and the analysis of geographic data is conceptualized. Spatial modeling exercises using the Model Builder technology of ArcGIS version 9 are also provided. Other topics covered include organizing data, planning a GIS project, creating derived data, and presenting results.
Includes index.
Keywords: ArcGIS; Geographic information systems; Graphical user interfaces (Computer systems).